Children and Adolescent Dental Age Estimation by the Willems and Al Qahtani Methods in Surabaya, Indonesia - Beshlina Fitri Widayanti Roosyanto Prakoeswa; Arofi Kurniawan; An’nisaa Chusida; Maria Istiqomah Marini; Beta Novia Rizky; Mieke Sylvia Margaretha; Haryono Utomo; Anugerah I’zaaz Darmawan; Andini Kamilia Nur Aisyah; Aspalillah Alias; Otty Ratna Wahjuni; Anand Marya (Hindawi, 2024)
Indexed by WOS/SCOPUS/ERA